The Uralic Trove (UraLaari) – The digital data infrastructure of speaker areas of Uralic languages and Finnish dialects - Vesakoski, Outi Karoliina; Dunn, Michael; Roose, Meeli; Santaharju, Jenni (Norway, 2026)
This paper presents the Uralic Trove, a collection of datasets related to the human past in the Uralic language speaker area with special focus on the area of Finland. All the datasets are made in large collaborations, and (apart from no 8) have initially been launched elsewhere – this paper aims at collecting a ‘trove’ where all these areal datasets are easily located. We briefly describe the contents of eight multidisciplinary open access datasets: The databases considering the whole Uralic family or its speaker area are 1) UraLex (a basic vocabulary database with cognate coding), 2) UraTyp (binary data of existence of given linguistic typological functions), 3) a Cartographical Database of Uralic Languages (GIS format) and another GIS database of Interdisciplinary Maps of North-West Eurasia. The Finnish datasets are more detailed and include 5) a digital, easy to use version of the Dialect Atlas of Finnish collected already 100 years ago, 6) AADA, Archaeological Artefact Database of Finland, 7) Historical Travel Environment model and 8) Historical Culture and Environment Database of Finland. Uralic Trove also includes two user interfaces, that are aimed for easy visualization and access of the data.
DHNB2024 Conference Proceedings Volume 2